NUCLEAR ENERGY - Igamberdiyev , Boburjon Tohirjon ugli; Xabibullayev, Xabibullo No‘monjon ugli; Xo‘jamberdiyev , Samandar Komiljon ugli (Educational Research in Universal Sciences, 2023)
Nuclear energy is a branch of energy that uses nuclear energy to obtain electrical and thermal energy, and is a branch of science and technology that deals with the theoretical development of methods and means of converting nuclear energy into electrical and thermal energy and their practical application.